Contexto familiar y su relación en la comprensión lectora de textos narrativos y descriptivos del área de comunicación en los estudiantes del 5° y 6° grado de primaria en las I.E Unidocentes del distrito de Rioja - Castro Arbildo, César Octavio (2011)
This research investigated the relationship of the family context in the reading comprehension of narrative and expository texts in the area of communication in students of 5th and 6th grade primary educational institutions one teacher in the district of Rioja, which became the general objective for the research. The problem arose because · of the experience gained during the development of professional practices, which they found certain deficiencies in the leaming of reading comprehension, which sparked interest in investigating the causes of these difficulties, agreed according to the background that family background factors resulted in educational, social and economic influence in the learning of reading comprehension which became the·hypothesis for this investigation. On the operational side, the research was conducted under a correlational design, counting a sample of 30 students to whom they were given a reading comprehension test. Similarly, a survey was applied to an equal number of parents to verify the characteristics of the family context in the educational, social and economic. As results, the verification of the hypothesis was done by Pearson correlation coefficient for a confidence level of 95% and a significance value of 0.05 and concluded that family background is significantly related to understanding reading the communication area in the students in fifth and sixth grade of primary one teacher in the educational institutions located in the district of Rioja. XV